The perspectives of interleukin-10 in the pathogenesis and therapeutics of multiple myeloma - Cheng-Der Liu; Chun-Chun Chang; Wei-Han Huang (Tzu Chi Medical Journal)
Multiple myeloma (MM) is typically featured by the increased levels of inflammatory cytokines in the neoplastic plasma cells (PCs) producing monoclonal immunoglobulin. PCs proliferate in the bone marrow, which will lead to extensive skeletal destruction with osteolytic lesions, osteopenia, or pathologic fractures. The diagnostic biology of MM has progressed from morphology and low-sensitivity protein analysis into multiomics-based high-throughput readout, whereas therapeutics has evolved from single active agent to potential active drug combinations underlying precision medicine. Many studies have focused on the cytokine networks that control growth, progression, and dissemination of the disease. The complexity of cytokines in MM development remains to be elucidated comprehensively. Apart from knowing that interleukin (IL)-6 is important in the pathogenesis of MM, it has been shown that IL-6 is a paracrine factor supplied by the microenvironment comprising of those cells from the myeloid compartment. Due to IL-10 was considered an immunosuppressive cytokine to promote cancer escape from immune surveillance, the role of IL-10 in this regard has been underestimated although recent advances have reported that IL-10 induces both PC proliferation and angiogenesis in MM. In addition, cumulative studies have suggested that IL-10 plays an important role in the induction of chemoresistance in many cancers; a virtual requirement of autocrine IL-10 for MM cells to escape from an IL-6-dependent proliferation loop was implicated. In this review, we summarize the available information to elucidate a new understanding of the molecular and functional roles of IL-10 in MM.